Industry 4.0 and customers satisfaction; evidence from fintech in emerging economy - Abdul, Falilat Ajoke; Olota, Oluwayomi; Balogun, Ebenezer; Babawale, Opeyemi (Universidad Francisco de Paula Santander, 2025)
In the age of technology, factors that contribute to customer satisfaction comprise data security, practicality, accessibility, and personalization. Hence, this study examined a detailed investigation into the relationship between Industry 4.0 advancements from Moniepoint Financial Technology and customer satisfaction. Specifically, the study examined; the impact of Digital Banking Platforms on Customers Convenience; the influence of artificial intelligence on customer personalization; the effect of automation on customer efficiency in Moniepoint Financial Technology. Descriptive design was adopted to survey 397 student customers of Moniepoint Financial Technology make up the population of the study. Structured questionnaire was used to gather data while SEM-PLS through SmartPLS 3.2.9 was used to analyze data. Findings revealed that digital banking, automation, and artificial intelligence are significant predictors of customer convenience, customer personalization and customer efficiency as factors of customer satisfaction respectively with r square value of 93.8%, 94.8%, and 88.2% respectively. The study concluded that industry 4.0 is statistically and positively significant to customer satisfaction in emerging economy fintech industry. It therefore recommended that investments in cutting-edge digital banking systems, such as chatbots, mobile banking applications, and virtual cards, should be given top priority by Moniepoint management since they greatly improve client convenience.